Adult T-cell leukemia/lymphoma - Oliveira,Pedro Dantas (2016)
Summary Adult T-cell leukemia/lymphoma (ATL) is a malignancy of mature CD4+ T-cells caused by human T-cell lymphotropic virus type 1 (HTLV-1). Twenty million people are believed to be infected throughout the world, mostly in Japan, Africa, the Caribbean, and South America, particularly in Brazil and Peru. ATL affects about 5% of infected individuals and is classified in the following clinical forms: acute, lymphoma, primary cutaneous tumoral, chronic (favorable and unfavorable), and smoldering (leukemic and non-leukemic). Although it is considered an aggressive disease, there are cases with a long progression. We emphasize the importance of clinical classification as an indispensable element for evaluating prognosis and appropriate therapeutic approach. Since several cases have been published in Brazil and this disease is still poorly known, we decided to make a review paper for dissemination of clinical, hematological and pathological aspects, diagnosis, and therapy. The best way to reduce the occurrence of ATL would be halting the transmission of the virus through breastfeeding.